2014
DOI: 10.12659/msm.890212
|View full text |Cite
|
Sign up to set email alerts
|

Carotid surgery affects plasma kynurenic acid concentration: A pilot study

Abstract: BackgroundAn increase in plasma kynurenic acid (KYNA) concentration has been observed following surgery, inflammation, and cerebral pathologies. The aim of the present study was to analyze the changes in plasma KYNA concentration in patients undergoing carotid surgery (CS).Material/MethodsAdult patients undergoing elective carotid endarterectomy (CEA) or carotid angioplasty with stent placement (CAS) were studied. Plasma KYNA concentrations were analyzed before surgery and at 4 time points after CS. The amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…They did not analyse a relationship between KYNA and NLR ratio, but they presented a similar trend of changes in plasma KYNA concentration and NLR. A relation between NLR and plasma KYNA concentration was observed by Terlecki et al ( 2014 ), who analysed changes in plasma KYNA concentration and NLR and found a strong correlation between mentioned parameters. In the present study, we also found a correlation between NLR and plasma KYNA concentration in patients anaesthetised intravenously.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…They did not analyse a relationship between KYNA and NLR ratio, but they presented a similar trend of changes in plasma KYNA concentration and NLR. A relation between NLR and plasma KYNA concentration was observed by Terlecki et al ( 2014 ), who analysed changes in plasma KYNA concentration and NLR and found a strong correlation between mentioned parameters. In the present study, we also found a correlation between NLR and plasma KYNA concentration in patients anaesthetised intravenously.…”
Section: Discussionmentioning
confidence: 70%
“…Persisted high plasma KYNA concentration has been noted in non-survived stroke traumatic patients and patients, who died after resuscitation (Darlington et al 2007 ; Ploder et al 2009 ; Ristagno et al 2013 ). Significantly higher plasma KYNA concentration has been found in carotid surgery patients with postoperative neurological dysfunctions (Terlecki et al 2014 ). KYNA has been also suggested as a marker of distress intolerance (Chiapelli et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%